Innovación en la Orientación Universitaria. Una experiencia : red de estudiantes mentores en la Universidad Complutense (REMUC) - Laura Oliveros Martín-Varés; Mercedes García García; Covadonga Ruiz de Miguel; Andrés Valverde Macías (Universidad de La Rioja, 2013)
In this work a mentoring experience at the university level is presented. The initiative, arised at the Department DOE-MIDE of the Faculty of Education of Seville in the course 2001-2002, has been adapted and implanted at the University Complutense of Madrid by a group of professors belonging to the Department of Methods of Investigation and Diagnosis in Education of the Faculty of Education. The description of the Net of Students Mentors in the University Complutense of Madrid (REMUC) is presented and includes: how the idea arised, the objectives, the phases that were necessary to make it reality, the structure and elements that composed it, the intervention pattern that sustains it, and the tools used. The development of the followed process is also described as well a as the evaluation and the experience's conclusions.